Intrauterine contraceptive device perforating the cecum, a pregnancy complication? - Luay Ibrahim Abu Atileh; Mohammad Anas Mourad; Dania Haj-Yasin; Laith Shlash; Laith Zaid Kaylani; Nardin Fadila (Wolters Kluwer Medknow Publications, 2019)
Intrauterine contraceptive device (IUCD) is a widely used method of contraception worldwide. Displacement of the IUCD extrauterine, by perforating the uterus and migration, is a serious complication following its insertion. We reported an extremely rare case of a 24-year-old female patient found to have a copper T 380A IUCD displaced from its normal site to be embedded into the cecum, suggested to have occurred during pregnancy, and being successfully removed laparoscopically.